Idiopathic cerebellar ataxia associated with celiac disease: lack of distinctive neurological features - Pellecchia, M. T. (BMJ Group, 1999)
OBJECTIVES—To determine the occurrence of celiac disease in a population of ataxic patients without definite diagnosis and to characterise distinctive features which may help to differentiate cerebellar ataxia with and without celiac disease. METHODS—Twenty four ataxic patients without definite diagnosis (group A) and 23 ataxic patients with definite diagnosis (group B) were screened for antigliadin (AGAs) and antiendomysium antibodies (EMAs). Patients with a positive AGA or EMA test underwent endoscopic biopsy of the duodenal mucosa. RESULTS—There was an increased prevalence of celiac disease in group A (3/24) compared with group B (0/23). None of the celiac patients presented gastrointestinal symptoms or malabsorption signs. None of the ataxic patients with celiac disease had early onset ataxia. CONCLUSIONS—Celiac disease is associated with ataxic syndromes without definite diagnosis, suggesting that it plays a part in the pathogenesis of some ataxic syndromes. The absence of distinctive neurological features in ataxic patients with celiac disease suggests that a search should be made for celiac disease markers in all ataxic patients without definite diagnosis.